STUDIES AND ANALYSIS OF A SOLAR-POWERED PESTICIDE SPRAYER - Zokhidov , Ikboljon Zokirjonovich (Educational Research in Universal Sciences, 2023)
This article delves into the development and analysis of hand sprayers utilizing non-traditional energy sources, with a specific focus on a solar-powered sprinkler pump. The primary objective is to address the agricultural needs in remote areas where fuel accessibility is a challenge. The article explores the design, components, and operational principles of the solar sprayer, emphasizing its advantages, such as simplicity, cost-effectiveness, and environmental friendliness. The study critically evaluates the drawbacks of conventional manually operated sprayers, highlighting limitations in capacity, operator fatigue, and the dependency on operator skill. Weather dependency, potential chemical exposure, and maintenance challenges are also discussed, providing a comprehensive overview of the existing issues with manual knapsack sprayers. It details the operational workflow of the solar sprayer and the associated benefits, emphasizing its potential to revolutionize agricultural practices. In conclusion, the article suggests the transition to solar-powered boom sprayers for enhanced efficiency and resource utilization in both small and large agricultural areas. The integration of innovative, eco-friendly technologies is seen as a key factor in increasing agricultural production efficiency while minimizing environmental impact.